Structure and transcription of the spinach chloroplast rDNA leader region. - Briat, J F (1982)
A cloned fragment of spinach chloroplast DNA carrying 140 bp of the 16S rRNA gene and 691 bp upstream this gene has been analysed by DNA sequencing, by in vitro transcription, by S1 mapping with chloroplast RNAs and purified 16S rRNA from 30S ribosomal subunits. A tRNAVal gene has been located between the position 394 and 465. Crude chloroplast RNA polymerase has been purified by heparin sepharose chromatography of a 80 000 g supernatant from pure lysed spinach plastids and used to transcribe the cloned Bg1 II-Pvu II DNA fragment. Four in vitro transcripts of about 830, 550, 350 and 260 bases were obtained whatever RNA polymerase used: the chloroplast or the E. coli enzyme. The transcripts of 550 and 260 bases are initiated by ATP. S1 mapping with in vivo chloroplasts RNAs on 5' labelled separated strands from Bg1 II-Pvu II fragments indicates 2 protected DNA fragments respectively of 140 and 260 bases on the strand which codes for rRNAs and possibly one protected DNA fragment of 550 bases on the other strand. The start site of the 260 bases transcript might correspond to the initiation site of transcription of the rRNA genes. The possibility that the 550 bases transcription of the non coding strand for rRNA genes corresponds to the beginning of a mRNA is discussed.